Noncompliance to Antihypertensive Medication in Patients with Essential Hypertension - Hussain Liaquat Memon, Syed Zafar Ahmed, Sher Muhammad, Abdul Bari Babar, Javeria, Ayaz Mir (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The most common and important treatable cause of non-communicable diseases is hypertension. Hypertension leads to high mortality and morbidity. The management of hypertension is not even close to the optimal target, despite the fact that there are effective, cheap, and safe drugs available in the markets of developing countries. Objective: This research aims to study antihypertensive therapy and examine the level of compliance with this therapy, along with the factors that contribute to non-compliance in this area. Study design: A cross-sectional study Place and Duration: This study was conducted at NICVD Karachi from December 2021 to December 2022. Methodology: All of the patients involved had hypertension, and they were adults. All the patients were those who regularly attended the hypertension clinic of this hospital, and they had been taking antihypertensive drugs for at least 1 month. A closed-ended questionnaire was used to interview the patients before the test was conducted. The data that was gathered through the questionnaire included gender, age, attendance of the patient at the hypertension clinic, patients having compliance with prescribed antihypertensive therapy drugs, and the reasons for non-compliance. Results: There were a total of 300 patients, of whom 150 were female and 150 were male. The mean age was 51 years. The majority of the participants were from the age group of 41 to 60 years, representing 52% of the participants. The majority of the hypertensive patients (65%) had poor compliance with the drugs they were prescribed. A total of 58% of the patients were not regular attendees at the clinic. Overall, 26% of participants stopped using the drugs because there were no symptoms seen after they started using them. Conclusion: The percentage of hypertensive patients who had poor compliance with the prescribed drugs was very high. Keywords: Adults, hypertension, compliance, antihypertensive drugs